Endogenous Direct Democracy: The Case of Mexico - Juve J. Cortés (Journal of Politics in Latin America, 2020)
Direct democracy (DD) – including initiatives and referendums – is increasingly used by citizens and governments to establish new policies around the world. Although framed as a tool that benefits citizens, it is also common for government actors, including parties, to utilise DD in initiating and pushing through new policies. To explain this puzzling development, existing research examines the regulative design of DD. Going a step further, this article explains how the design of DD originates. Using process tracing methodology, I examine the case of Mexico – the most recent adopter of DD in 2014 – and illustrate how, when, and how DD can be used and modified. I argue that DD is endogenous: we cannot conceive of it independently of the political forces that generated it. Other prominent cases, such as Uruguay, suggest that DD was adopted to pursue party goals or to shape a particular government structure. Legislatures certainly provide the masses the option of engaging in DD but they do so on their own terms.